A Systematic Review and Meta-Analysis Protocol of Chemoablation vs. Transurethral Resection of Bladder Tumor in Patients With Non-Muscle-Invasive Bladder Cancer - Shi, Xu; Feng, Dechao; Wei, Wuran (Frontiers in Surgery, 2021)
Background Chemoablation therapy, or chemoresection, is an alternative to the treatment of non-muscle-invasive bladder cancer (NMIBC) next to transurethral resection of bladder tumor (TURBT). Because TURBT cannot be applied to all NMIBC patients, and some patients is expected to receive neoadjuvant chemotherapies (NAC) such as chemoablation to achieve tumor degradation. The concept of NMIBC chemoablation deserves further evaluation. Since no related meta-analysis has been published, the present study is designed in order to discuss which treatment is superior to another between ablation and TURBT in patients with NMIBC. Methods and analysis Our research sources include PubMed, Web of Science, Cochrane library, the Cochrane Controlled Register of Trials (CENTRAL) and Chinese electronic databases, including China National Knowledge Infrastructure, Wan Fang database, VIP, SinoMed and the Chinese Clinical Trial Registry. The searches will cover the period from August 1994 to the time of the submission of this review. There will be no limitations on language, and all articles will be screened and collected by two reviewers independently. We will analyze the data using RevMan version 5.3, or Stata software, and the conduction of study will refer to the Cochrane Handbook for Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocol guidelines. The main outcome will be clinical effectiveness (complete response rate, recurrence rate, time to recurrence, progression rate as defined by study authors, time to progression, overall duration of survival, cancer-specific mortality, time to mortality due to bladder cancer, etc.). The secondary outcomes mainly include safety (adverse events, pain, length of hospital stay and tolerability, etc.)